Betty & Veronica spectacular - Gladir, George 1925-2013; Golliher, Bill; Parent, Dan (Archie Comic Publications, 2018)
The first of a chronological collection featuring the magazine-format series spotlighting Riverdale's iconic duo. See how B&V tackle the world of fashion, prep for the red carpets of Hollywood--and still have time to finish their homework
Title from indicia
"All stories previously published ... by Archie Comic Publications, Inc. (or its predecessors) in magazine form 1992-1994.
Keywords: Jugend; Freundschaft; Mädchen; Riverdale -- Imaginärer Schauplatz; Comic